Intégration de la préparation physique dans l’approche ergonomique : quel dispositif pour quel(s) objectif(s) ? - Céline Uguen; Sandra Sablon; Gabriel Carballeda (Activités)
The article presents a case of ergonomic intervention proposing the physiological preparation of workers as a tool for the prevention of musculo-skeletal disorders in the agri-food sector. In a business whose activities have strong organizational and physiological constraints, the leverage to introduce this kind of practice is questioned. The implementation of warm-ups within a company requires, on the one hand, to have both ergonomic and physical preparation skills. On the other hand, a specific social construction of the intervention would be asked for. Finally, the conditions for success of the project both from the point of view of the stakeholders and the company should be laid beforehand to ensure the success of the overall prevention process.